Gemini optical observations of binary millisecond pulsars. Issue 4 (15th September 2015) - Testa, V.; Mignani, R. P.; Pallanca, C.; Corongiu, A.; Ferraro, F. R.
Abstract: Millisecond pulsars (MSPs) are rapidly spinning neutron stars, with spin periods P s ≲ 10 ms, which have been most likely spun up after a phase of matter accretion from a companion star. In this work, we present the results of the search for the companion stars of four binary MSPs, carried out with archival data from the Gemini South telescope. Based upon a very good positional coincidence with the pulsar radio coordinates, we likely identified the companion stars to three MSPs, namely PSR J0614−3329 ( g  = 21.95 ± 0.05), J1231−1411 ( g  = 25.40 ± 0.23), and J2017+0603 ( g  = 24.72 ± 0.28). For the last pulsar (PSR J0613−0200) the identification was hampered by the presence of a bright star ( g  = 16 ± 0.03) at ∼2 arcsec from the pulsar radio coordinates and we could only set 3σ upper limits of g  = 25.0, r  = 24.3, and i  = 24.2 on the magnitudes of its companion star. The candidate companion stars to PSR J0614−3329, J1231−1411, and J2017+0603 can be tentatively identified as He white dwarfs (WDs) on the basis of their optical colours and brightness and the comparison with stellar model tracks. From the comparison of our multiband photometry with stellar model tracks we also obtained possible ranges on the mass, temperature, and gravity of the candidate WD companions to these three MSPs. Optical spectroscopy observations are needed to confirm their possible classification as He WDs and accurately measure their stellar parameters.